Muslims in Georgetown world heritage site: cultural and socio-economic sustainability / Jamalunlaili Abdullah … [et al.] - Abdullah, Jamalunlaili; Azam, Rahmat; Bustami, Reevany; Ahmad, Che Bon (Universiti Teknologi MARA Cawangan Selangor, 2018)
Georgetown World Heritage Site (GWHS) is known as a potpourri of various ethnic groups who have settled in the area during various periods of the past 300 years. Chinese are the majority although Muslims (Malays) were earliest settlers and once the majority. This paper analyzes the socio-economic and cultural sustainability of the Muslim community within the GWHS relying on historical records and current situation. Areas around masjid kapitan Kling and masjid Melayu are considered as the Muslim enclave. While the Indians Muslims are doing rather well socio-economically, the same cannot be said of the Malays. The number of Malays is very low and Malay business owners in the area tend to live outside the GWHS. The decline of the Muslim population has grave implications to the socio-economic and cultural sustainability of the Muslims, especially the Malays.